Modeling and resonance suppression control for electro-hydrostatic actuator as a two-mass resonant system. (2nd January 2018) - Sakuma, Tomoki; Tsuda, Kenta; Umeda, Koudai; Sakaino, Sho; Tsuji, Toshiaki
Abstract: Electro-hydrostatic actuators (EHAs) possess excellent power/weight ratio and space-saving properties. However, uncertainty exists with respect to the presence of non-linear behaviors and dynamic characteristics. Servo pumps, hydraulic motors, and oil-filled pipes can be regarded as motors, loads, and springs, respectively. Hence, EHAs can be modeled as two-mass resonant systems. In this paper, we show a parameter identification method for modeling EHAs as two-mass resonant systems. Then, in order to suppress the effect of resonance, self-resonance cancellation technique is implemented. As a result, phase delay is significantly improved in the position tracking. Graphical Abstract: